The role of online brand community engagement on positive or negative self-expression word-of-mouth - Loureiro, S. M. C.; Kaufmann, H. R. (Cogent Business and Management, 2018)
The aim of this research is to explore how online engagement influences positive versus negative consumption-focused self-expression word-of-mouth. Three brands are selected to be the focus of the study (Starbucks, Apple, and McDonald's), and six online brand communities of these brands participated. The online questionnaire was distributed to those communities and filled in by 600 members of the respective love and hate brand communities. Affection (passion/aversion) is the motivational factor that leads community members of both types (love and hate) to be active in commenting and writing reviews about the product/brand. In hate brand communities, connecting negatively influences consumption-focused self-expression word-of-mouth, whilst brand influence has a positive effect on it.